Conceptual model of care during infancy from Islam perspective - Soheila Jafari-Mianaei; Nasrollah Alimohammadi; Marzieh Hasanpour; Amir-Hosein Bank (Tehran University of Medical Sciences, 2020)
Background & Aim: Each conceptual model in nursing seeks to explain the fundamental concepts of the discipline based on the culture and values of societies in order to be used more effectively, as a scientific and practical framework. The aim of this study was to design a conceptual model of care during infancy from Islam perspective. Methods & Materials: The conceptual model used in this study was designed based on the model synthesis process developed by Walker and Avant (2011) in three steps in 2017: Concept development and specifying focal concept, statement synthesis and identifying connections between concepts, systematic organization of connections and building an integrated representation. Qur'an and its interpretation books and Shiite Hadith books were of the resources. Results: As a result of developing the concept of "care during infancy in terms of Islam", six concepts were synthesized. "Infant as a person with dignity and potential for excellence" was as the focal concept. Other concepts included "basic principles of nurturing", "parents as the representatives of God in nurturing infants", "mother as the symbol of creativity and divinity of God", "healthy and competent child", and "God as the merciful nurturer". After defining connections between the concepts, the structure of conceptual model was presented. Conclusion: Infant care is nurturing a human being who has dignity, rights and potential for excellence from the time of conception. From Islam perspective, God is the eternal nurturer who nurtures the infant with kindness and dignity, and mother is the manifestation of the creativity and divinity of God. The infant is entrusted to the parents by God, and parents are the agents of God who lay the groundwork for nurturing the infant. In order to have a healthy and competent child, observing the principles of nurturing is important. "Care during infancy from Islam perspective" model is a conceptual model that can be used for the development of applied theories, clinical practice, research, and education of nursing students and the community.